The role of parents, schools, and social media use in influencing civic engagements of school adolescents in government schools in Addis Ababa - Bogale, Azmeraw Belay; Kibret, Belay Tefera (Bahir Dar Journal of Education, 2023)
The study examined how parents, schools and social media use influenced civic engagements of school adolescents. It also assessed the mediation role of sense of community and perceived civic competence. Participants were 960 school adolescents (mean age = 17.7, range: 15-19 years; 53.5% females) who were selected using multistage sampling technique. The study employed a correlational design, conducted confirmatory factor analysis, and used structural equation modeling to investigate the direct and indirect (mediated) effects of parental civic socialization, school civic experiences and social media, and independent and combined contributions of predictors on civic engagement. Results have shown that parental civic socialization influenced more on perceived civic competence than sense of community connectedness. School civic experience had a direct influence both on students’ sense of community connectedness and perceived civic competence. The influence of social media use on sense of community and perceived civic competence was not significant. All variables, except school civic experience predicted civic engagement. Parental civic socialization and school civic experience showed statistically significant indirect (mediated) effects on civic engagement, through sense of community and perceived civic competence. Social media use influenced civic engagement directly; however, the mediated effect of sense of community connectedness and perceived civic competence was not statistically significant. Conclusions and recommendations in light of the implications of findings for educational practice and parenting are drawn.